Nghiên cứu tổng hợp vật liệu MOF Cu3(BTC)2(MOF-199) bằng phương pháp thủy nhiệt - Anh, Nguyễn Duy; Hoài Phương, Nguyễn Thị; Dương, Lã Đức; Ngãi, Đoàn Thị (Vietnam Journal of Chemistry, 2015)
Cu3(BTC)2 MOF material was successfully synthesized by using hydrothermal method at temperature of 100 oC in auctoclave. Cu3(BTC)2 was analysed its components and microscope structure form by using x-ray diffraction (XRD), infrared spectroscopy (IR), scanning electron microscope (SEM), thermal analysis (TGA), BET. This material has octahedral crystal structure, size from 2 to 10 µm, thermal stability at 300 oC and 1460 m2/g surface area.